SEBARAN DAN EFIKASI BERBAGAI GENUS CENDAWAN ENTOMOPATOGEN TERHADAP Riptortus linearis PADA KEDELAI DI LAMPUNG DAN SUMATRA SELATAN - Yusmani Prayogo . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Distribution and efficacy on various entomopathogenic fungi at Lampung and South Sumatra as a biological control agent against Riptortus linearis. This study was conducted from June to September 2005. The fungi were isolated from insect cadavers, insect bait, and soil sample from the soybean land. Each fungal sample was identified base on their morphology using determination keys. The fungal isolates were inoculated to the pod sucking bug Riptortus linearis. The results showed that there were six genera of entomopathogenic fungi that can be isolated, i.e. Fusarium sp., Penicillium sp., Metarhizium sp., Verticillium sp., Paecilomyces sp., and Beauveria sp. The fungus-induced mortality of R. linearis varied between 5 - 30%. Paecilomyces sp. isolated from Lebak Batang Baru induced 25%; Beauveria sp. isolated from Pulung Kencana 25%; Verticillium sp. isolated from Kaliungu 20%. Metarhizium sp. isolated from Terbanggi Subing 20% and Verticillium sp. isolated from Lebak batang Baru 20% mortality. It was suggested that these fungi have potential as biological control agents for the pod sucking bug in dry acid land.